Hierarchical structures of β-TCP/45S5 bioglass hybrid scaffolds prepared by gelcasting - Lopes, João Henrique; Magalhães, Jéssica Aparecida; Gouveia, Rubia Figueredo; Bertran, Celso Aparecido; Motisuke, Mariana; Camargo, Samira E.A. [UNESP]; Trichês, Eliandra de Sousa (Elsevier, 2016)
This paper investigates the microstructure and the mechanical properties of β-tricalcium phosphate (β-TCP) three-dimensional (3D) porous materials reinforced with 45S5 bioactive glass (BG). β-TCP and β-TCP/x%-BG scaffolds with interconnected pores networks, suitable for bone regeneration, were fabricated by gel-casting method. Mechanical properties, porosity, and morphological characteristics were evaluated by compressive strength test, scanning electron microscopy (SEM) and X-ray microtomography analysis, whereas the structures were fully explored by XRD, and Raman spectroscopy. To the best of our knowledge, this is the first time where the mechanism for understanding the effect of bioglass on the mechanical properties and microstruture of β-TCP/45S5-BG scaffolds has been systematically studied. The findings showed that ionic product lixiviated from 45S5 bioactive glass, rich in silicon species and sodium ion, catalyzes a phase transition from β-TCP to Si-TCP by replacement of phosphorus for silicon and contributes to the improvement of scaffolds mechanical properties. The compressive strength of β-TCP/5%-BG and β-TCP/7.5%-BG was improved around 200% in comparison to pure β-TCP. Osteoblast-like cells (MG 63) were exposed to the materials for 24 h through the use of medium conditioned by β-tricalcium phosphate/bioactive glass. Cell viability was measured by MTT assay in the cells and the data obtained were submitted to ANOVA, Tukey[U+05F3]s multiple comparison (p<0.05). The β-TCP/7.5-BG promoted an increase of cell proliferation. The results suggest that compositions and processing method studied may provide appropriate materials for tissue engineering.
Keywords: 45S5 bioglass; Bioactivity; Gelcasting; Scaffolds; β-TCP